Practicarea ilegală a activităţii de întreprinzător: modalitatea normativă specificată la lit.b) art.125 din Codul Penal [Articol] - Ulianovschi, Gheorghe; Băbălău, Denis (CEP USM, 2016)
În cadrul analizei realizate în acest articol se stabileşte că, în prezenţa modalităţii prevăzute la lit.b) art.125 CP RM, fapta prejudiciabilă adoptă forma acţiunii. Se arată că situaţiile prevăzute la alin.2 şi 3 art.10 al Legii cu privire la antreprenoriat şi întreprinderi urmează a fi disociate de situaţia consemnată a alin.1 art.10 al aceleiaşi legi. Se demonstrează că articolul 241 CP RM (coroborat cu lit.b) art.125 CP RM) se află într-o relaţie de concurenţă dintre parte şi întreg cu art.242 CP RM. Se ajunge la concluzia că ipoteza privind desfăşurarea unor genuri de activitate, permise în mod exclusiv întreprinderilor de stat, nu se regăseşte în dispoziţia de la lit.b) art.125 CP RM şi, implicit, în dispoziţia de la art.241 CP RM. Se relevă că răspunderea pentru desfăş urarea unor genuri de activitate, permise în mod exclusiv întreprinderilor de stat, poate fi doar cea stabilită de alin.4 art.10 al Legii cu privire la antreprenoriat şi întreprinderi. Se argumentează că desfăşurarea activităţii de întreprinzător fără licenţă nu se regăseşte în dispoziţia de la lit.b) art.125 CP RM. În astfel de cazuri, răspunderea se aplică în baza alin.(4) art.263 din Codul contravenţional. În asemenea cazuri, nu este exclusănici aplicarea unei norme care este specială în raport cu alin.(4) art.263 din Codul contravenţional (de exemplu: lit.l) art.169, art.179, alin.(1)-(3) art.197, 248, alin.(2) art.2771, alin.(2) art.284, alin.(1) art.2932 sau altele din Codul contravenţ ional). De asemenea, poate fi aplicat art.214 sau 2456 CP RM. Nu în ultimul rând, se stabileşte: calificarea desfăşurării activităţii de întreprinzător fără licenţă în baza art.241 CP RM (coroborat cuit.b) art.125 CP RM) ar însemna nu altceva decât aplicarea prin analogie a legii penale, interzisăde alin.(2) art.3 CP RM.

Within this article, as a result of the performed analysis, it is established that, in the presence of the normative proceeding provided by lett.b) art.125 PC RM, the prejudicial act of the offence in question is committed through the mean of action. It is shown that the situations referred to at par.2 and par.3 art.10 of the Law on entrepreneurship and enterprises are to be considered separately from the situation re corded at par.1 art.10 of the same law. It is argued that art.241 PC RM (in conjunction with lett.b) art.125 PC RM) is in competition of part and whole with art.242 PC RM. On this issue, it is concluded that the possibility of cond ucting certain types of activities, allowed exclusively for state enterprises, is not provided by the provision of lett.b) art.125 PC RM, and thus is not provided by the provision of art.241 PC RM as well. It is pointed out that the liability for conducting certain types of activities, allowed exclusively for state enterprises, can only be established under par.4 art.10 of the Law on entrepreneurship and enterprises. It is argued that the act of conducting unli censed entrepreneurial activity is not specified in the provision of lett.b) art.125 PC RM. In such cases, the liability is established under par.(4) art.26 3 of the Contravention Code. Also, we cannot rule out the possibility of applying a special norm in relation to par.(4) art. 263 of the Contravention Code (e.g.: lett.l) art.169, art.179 , par.(1)-(3) art.197, art.248, par.(2) art.277 1 , par.(2) art.284, par.(1) art.293 2 or other articles of the Contravention Code). We can also apply art.214 or art.245 6 PC RM. Finally, but not least important, within this article it is pointed out that the qualification of the act of conducting unlicensed entrep reneurial activity under art.241 PC RM (in conjunction with lett.b) art.125 PC RM) would only mean to apply by analogy the penal legislation, which is withheld under the provision of par.(2) art.3 PC RM.
THE ILLEGAL PRACTICE OF ENTREPRENEURI AL ACTIVITY: THE NO RMATIVE PR OCEEDING REFERRED TO AT LETT.B) ART.125 OF THE PENAL CODE
Keywords: acţiune; inacţiune; activitate de întreprinzător; action; inaction; entrepreneurial activity